Exploring The Implementation of Total Physical Response (TPR) in Facilitating Vocabulary Learning and Speaking Participation At a Vocational High School - Izzah Putri Ramadhania; Henny Dwi Iswati (International Journal of Technology and Education Research, 2026)
This study investigates the implementation of Total Physical Response (TPR) in facilitating vocabulary acquisition and speaking participations among vocational high school students. The research was motivated by students’ limited vocabulary mastery, low confidence in speaking English, and minimal participation in classroom communication activities. Considering the practical and kinesthetic characteristics of vocational education, TPR was selected as an interactive learning method that integrates language instruction with physical movement to create a more engaging learning environment.The study aimed to examine how TPR was implemented in English learning and to explore its role in supporting students’ vocabulary learning and speaking participation. This research employed a qualitative descriptive approach conducted at SMK PGRI 1 Sidoarjo. The participants consisted of one English teacher and ten tenth-grade students selected purposively. Data were collected through classroom observations conducted over four meetings and semi-structured interviews with the teacher and students. The data were analyzed through data reduction, categorization, interpretation, and conclusion drawing. The findings revealed that the implementation of TPR encouraged active student participation, improved vocabulary comprehension through action-based instruction, and increased students’ confidence in speaking activities. The integration of gestures, commands, and contextual practice helped students understand and retain vocabulary more effectively while reducing anxiety in oral communication. In conclusion, TPR provides a practical and contextual approach to English language learning in vocational high schools and can serve as an effective alternative method for facilitating vocabulary development and speaking participation.